Reflection and transmission of seismic waves under initial stress at the earth's core-mantle boundary - Sukhendu Dey; Sushil Kumar Addy (International Journal of Mathematics and Mathematical Sciences)
In the present paper the influence of the initial stress is shown on the reflection and transmission of P waves at the core-mantle boundary. Taking a particular value of the inherent initial stress, the variations of reflection and transmission coefficients with respect to the angle of emergence are represented by graphs. These graphs when compared with those having no initial stress show that the effect of the initial stress is to produce a reflected P and S waves with numerically higher amplitudes but a transmitted P wave with smaller amplitude. A method is also indicated in this paper to calculate the actual value of the initial stress near the core-mantle boundary by measuring the amplitudes of incident and reflected P waves.